Optimalisasi Pemanfaatan Website Sebagai Media Pemasaran Digital untuk Meningkatkan Penjualan Maincamacama.Playtime di Kota - Farhan Rabbani Nayuan; Ismail Zikri, Tubagus Muhammad (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The use of websites in the realm of digital marketing serves as a form of owned media that plays a significant role in marketing activities, particularly in applying brand identity and enhancing as well as simplifying the process of product sales. Maincamacama.Playtime is a company with strong potential to implement website utilization in its digital marketing efforts and product sales. The goal is to optimize website use to support sales by prioritizing the application of brand identity in its visual design, considering functionality, and adopting the Competitor-Based Design method in the design process. The project began with observations of the company’s internal and external conditions, followed by needs analysis, and continued to the website design phase as a digital marketing medium. The results of this project indicate that website utilization can enhance and streamline the sales process, strengthen the company's brand identity, and deliver a better user experience.